Diagnostic and Predictive Values of LAP in Hypertension: A Cross-Sectional Study in Chinese Population Older Than 65 Years - Shuo Yan; Qing-Hu Zheng; Dong-Mei Sun; Ying Wu; Tu-Ming Li; Ping Zhong (International Journal of Hypertension)
This study aimed to investigate the predictive value of lipid accumulation product (LAP) in hypertension in Chinese population older than 65 years. A total of 2092 adults from the communities in Pudong New Area of Shanghai were included in this cross-sectional study. The participants filled in questionnaire and received anthropometric and laboratory examinations. The receiver operating characteristics curve (ROC) was used to analyze the predictive value of different risk factors in hypertension. Results showed that LAP was closely related to hypertension (adjusted OR: 1.011, 95% CI: 1.007–1.015). In females, LAP, fasting blood glucose (FPG), and body mass index (BMI) were associated with hypertension; in males, triglycerides (TG) and waist circumference (WC) were related to hypertension. LAP (AUC = 0.655, 95% CI: 0.632–0.679) was better than neck circumference (NC) and BMI in predicting hypertension. When the cutoff value was 33.5, LAP had the best predictive performance. In males, LAP at 36.72 and 56.76 had the best predictive performance in males (AUC = 0.663, 95% CI: 0.629–0.697) and females (AUC = 0.650, 95% CI: 0.618–0.682), respectively. In conclusion, LAP is a risk factor of hypertension in the elderly. For hypertension, BMI, FPG, and LAP have favorable predictive performance in females, and WC and TG have better predictive performance in males.